(untitled) - Malek, Mohammad A. (New York, NY., 2004)
The ASME (American Society of Mechanical Engineers) Boiler codes are known throughout the world for their emphasis on safety and reliability. Written by an expert with practical experience in boiler inspection and maintenance, this book offers a clear, straightforward interpretation of the codes.
Keywords: Steam boilers; Design and construction